Does Reporting Decrease Corruption?. (January 2014) - Bone, John; Spengler, Dominic
We construct two variants of a three-player one-shot corruption game, one in which reporting on bribers is cumbersome and one in which it is rewarded (profitable). Both variants feature a briber who can bribe or not, an official who can reciprocate or not and an inspector who can inspect or not. In the first variant, the official accepts the bribe by reciprocating or simply rejects the bribe by choosing not to reciprocate. In the second variant, the official either accepts and reciprocates or rejects and reports the bribe. Under successful inspection, offending players receive separate penalties, which can be varied asymmetrically. Under plausible assumptions about the values of payoff parameters, we obtain a mixed-strategy Nash equilibrium in both variants, akin to Tsebelis' inspection game. We obtain two interesting results. First, marginally changing the penalties moves the equilibrium probabilities in both games in the same directions, suggesting robustness of the model. We find that larger penalties on the briber increase the overall probability of reciprocated bribery, that is, corruption, while larger penalties on the official decrease corruption. Second, when comparing the two models, we obtain the surprising result that the probability of reciprocated bribery (corruption) is higher in the variant where the official is rewarded for reporting on the briber. JEL: K42, H00, C72, O17